Qualitative research : issues of theory, method and practice - Silverman, David (Los Angeles : Sage, 2011)
This text follows the broad sequence of David Silverman's "Interpreting Qualitative Data" and can be used as: an accompaniment focusing on more in-depth analysis and application; a supplement to any introductory text on qualitative research; and as a free standing textbook.
Includes bibliographical references and indexes.
Keywords: Social sciences -- Research; Social sciences -- Methodology